2017
DOI: 10.1007/978-3-319-58747-9_7
|View full text |Cite
|
Sign up to set email alerts
|

Palindromic Decompositions with Gaps and Errors

Abstract: Identifying palindromes in sequences has been an interesting line of research in combinatorics on words and also in computational biology, after the discovery of the relation of palindromes in the DNA sequence with the HIV virus. Efficient algorithms for the factorization of sequences into palindromes and maximal palindromes have been devised in recent years. We extend these studies by allowing gaps in decompositions and errors in palindromes, and also imposing a lower bound to the length of acceptable palindr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…We start with maximal palindromic factorization presented by [2] in section 2. Later, we explain palindromic factorization with gaps, maximal palindromic factorization with errors and maximal palindromic factorization with gaps and errors presented by [1] in sections 3, 4 and 5.…”
Section: General Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…We start with maximal palindromic factorization presented by [2] in section 2. Later, we explain palindromic factorization with gaps, maximal palindromic factorization with errors and maximal palindromic factorization with gaps and errors presented by [1] in sections 3, 4 and 5.…”
Section: General Definitionsmentioning
confidence: 99%
“…In this section we present an an efficient solution to the Palindromic Factorization with Gaps problem has been introduced by Adamczyk et al [1] .…”
Section: Palindromic Factorization With Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally it was shown that the upper bound on the number of palindromic factors of a string coincides with the lower bound on the number of closed factors (see [3] and references therein). Thus the study of closed strings shows potential applications in connection with applications of palindromes [4]. On the algorithmic side Badkobeh et al in [2] presented (among others) an algorithm for the factorisation of a given string of length n into a sequence of longest closed factors (LCFs) in time and space O(n) and another algorithm for computing the longest closed factor starting at every position in the string in O(n log n log log n ) time and O(n) space.…”
Section: Introductionmentioning
confidence: 99%
“…In molecular biology, for instance, palindromic sequences are extensively studied: they are often distributed around promoters, introns, and untranslated regions, playing important roles in gene regulation and other cell processes (see e.g. [4] [10]).…”
Section: Introductionmentioning
confidence: 99%